2015
DOI: 10.1186/s12938-015-0100-y
|View full text |Cite
|
Sign up to set email alerts
|

The repair of full-thickness articular cartilage defect using intra-articular administration of N-acetyl-d-glucosamine in the rabbit knee: randomized controlled trial

Abstract: BackgroundAlthough various alterative models of therapy are used for cartilage repair, no definite conclusion has been reached. Glucosamine (GlcN) is widely used as a nutritional supplement. However, the clinical- evidence-based outcome of GlcN administration remains controversial. N-acetyl-d-glucosamine (GlcNAc), a derivative of GlcN, shows chondroprotective activity and mediates the activation of articular chondrocytes. Therefore, we investigated the effect of intra-articular administration of GlcNAc in rabb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Previous studies have described neo-hyaline cartilage tissue formation as gene expression of COL2A1 and higher glycosaminoglycan content. 18,36 Furthermore, extracellular matrix proteins (e.g., ACAN, DCN, COMP, and HAPLN1) are highly expressed in human cartilage and human articular chondrocytes. 24,26,37 In our studies, both cell types respond to hypoxia by enhancing the expression of several chondrogenic markers including SOX9, HAPLN1, and COMP, but also HIST2H4 and HIF1A.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described neo-hyaline cartilage tissue formation as gene expression of COL2A1 and higher glycosaminoglycan content. 18,36 Furthermore, extracellular matrix proteins (e.g., ACAN, DCN, COMP, and HAPLN1) are highly expressed in human cartilage and human articular chondrocytes. 24,26,37 In our studies, both cell types respond to hypoxia by enhancing the expression of several chondrogenic markers including SOX9, HAPLN1, and COMP, but also HIST2H4 and HIF1A.…”
Section: Discussionmentioning
confidence: 99%
“…However, repetitive mechanical loading and many pathologic factors can cause cartilage damage in the general and athletic populations [ 4 , 5 ]. The cartilage lesion patients usually suffered from pain, swelling, and joint locking [ 6 ], which eventually lead to progressive damage and degenerative diseases, namely, osteoarthritis (OA) which is the leading cause of physical disability [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shikhman et al proved that intramuscular injections of GlcNAc provide better chondroprotective and anti-inflammatory activity than HA in an anterior cruciate ligament transection model of OA using rabbits [13, 19]. In addition, our previous study demonstrated that intra-articular administration of GlcNAc promoted the repair of full-thickness articular cartilage defects in a rabbit knee joint model [20]. However, HA is another signal we used to compare osteochondral regeneration with GlcNAc.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, intra-articular injection of GlcNAc could only promote the repair of experimental FTAC defects in the rabbit knee joint model [20]. However, lack of support from the scaffolds could cause subchondral bone overgrowth [24, 25].…”
Section: Introductionmentioning
confidence: 99%